Sustainable characteristics of traditional villages: a systematic literature review based on the four-pillar theory of sustainable development - Zheng, Xiaoli; Herman, Siti Sarah; Abdulkareem Salih, Sarah; Ismail, Sumarni (Multidisciplinary Digital Publishing Institute, 2024)
The definition of sustainable characteristics of traditional villages can assist in determining the direction of development and evaluating the development results. Nevertheless, a clearly defined concept of the sustainable performance of traditional villages is required. (1) This paper addresses the phenomenon of traditional villages and their decline due to urbanization, industrialization, and the movement of people from rural settlements. The development of traditional villages causes several concerns. This study aims to present a more precise definition of the sustainability of traditional villages. (2) the Preferred Reporting Items for Systematic Evaluation and Meta-Analysis (PRISMA) guidelines conducted a systematic literature review. The data were searched using the Web of Science database, with consideration given to the values of relevance, authority, and impact. (3) The sustainability of traditional villages is explained based on the four-pillar theory of sustainable development, focusing on the economic, environmental, social, and cultural dimensions. (4) The findings provide a scientific framework for understanding the sustainability of traditional villages. These results will provide insights to the future preservation and development of traditional villages.